Pengaruh Religiusitas Dan Kebersyukuran Terhadap Perilaku Berzakat Harta - Ahda Segati; Abdul Latif Rizqon (Universitas Darussalam Gontor, 2021)
The purpose of this study was to determine how the influence of religiosity and gratitude on the behavior of zakat in the Pekanbaru community. The data used in this study is primary data as many as 100 respondents as a sample who have implemented Zakat Mal in Pekanbaru. Data obtained by questionnaire using Likert scale. The research model is multiple linear regression by using religiosity and gratitude as independent variables, while tithing behavior is the dependent variable. The data is then processed with the SPSS program to answer research questions. The results showed that there was a significant influence between religiosity and gratitude on the behavior of zakat in the Pekanbaru community.